PENILAIAN PENGARUH MODAL KERJA, SIMPANAN ANGGOTA DAN PINJAMAN ANGGOTA TERHADAP PEROLEHAN SHU KOPERASI KEPOLISIAN (PRIMKOPOL) POLDA NTB - Ahmad Adroma Aji; Isnawati Isnawati (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2025)
One of the indicators of a cooperative's success can be seen from the improved distribution of Sisa Hasil Usaha (SHU) each year. SHU is obtained when the cooperative's income exceeds the expenses incurred during a specific period, and a significant portion of the cooperative's income is derived from interest on loans taken by its members. This study aims to analyze the influence of working capital, member savings, and member loans on the distribution of SHU at the Koperasi Kepolisian (PRIMKOPOL) POLDA NTB. This research employs a quantitative approach with a causal method, aiming to identify the cause-effect relationship between variables. The population of this study consists of the financial reports of PRIMKOPOL from 2019 to 2023. Data were collected through document studies and interviews with cooperative management and selected members. The variables examined include working capital, member savings, and member loans as independent variables, and SHU as the dependent variable. The data were analyzed using multiple linear regression. The results indicate that working capital and member savings do not significantly influence the distribution of SHU, while member loans have a significant effect on the distribution of SHU at the Koperasi Kepolisian (PRIMKOPOL) POLDA NTB